Implementation of Big Data Analytics and its Challenges in Digital Transformation Era: A Literature Review - Susanto, Firsty Larastiyana; Maulani, Agustin; Nuri, Siti Nuran (International Journal of Informatics and Information Systems, 2024)
The reliance on technology to support various aspects of human life has become very relevant and significant. The steadily increasing volume of data (called big data) plays an important role in machine learning, Internet of Things (IoT) and other intelligence applications. The interaction between big data and operations in various aspects of human life is a concern, this systematic literature review provides a descriptive aspect of the literature review, the research results offer a comprehensive overview of existing big data implementations ranging from 2019 to 2023. Other than this, we discuss the general challenges for researchers in using various big data sources in different crises. This study, especially revealing the implementation and challenges of big data in general, is expected to provide a knowledge base for researchers to delve deeper and more specifically.